Relative Distribution and Amount of Different Types of Astigmatism in Mixed Ethnic Population of Karachi - Adnan Afaq, Tabassum Ahmad, Khwaja Sharif-ul-Hasan, Muhammad Zia-ul-Haque Ansari, Abrar Ali (Pakistan Journal of Ophthalmology, 2009)
Purpose: Astigmatism is a common refractive problem and is especially significant in children because of its effect on visual development. In this article we have analysed relative distribution of different types and amount of astigmatism in the mixed ethnic population of Karachi. Material and Methods: Records of 914 eyes with astigmatic error in a clinic based set up were analysed retrospectively. Streak retinoscope was used for refraction and sphero cylindrical method was used to minutely neutralize the reflex. Half diopter cross cylinder was used to verify and refine the power and axis of cylindrical lens. Any error, stigmatic (spherical) or astigmatic (cylindrical) of ¼ diopter or more was considered an error and included in the analysis. Result: Astigmatic error was present in 914 of the 1898 eyes with ametropia (48.16%). Of the 914 eyes with astigmatism, myopic astigmatism was present in 700 eyes (76.60%), hypermetropic astigmatism in 175 eyes (19.14%), and mixed astigmatism in 39 eyes (4.26%). Of the 914 eyes with astigmatism, mild astigmatism (1/4 to 1 D) was present in 616 eyes (67.40%), moderate astigmatism (>1-2 D) in 247 eyes (27.02%), and high astigmatism (>3 D) in 51eyes (5.58%). Conclusion: Myopic astigmatism was the major type of astigmatic error found in the mixed ethnic population of Karachi city in the age group from 1 to 40 years. Astigmatism >1 D was found in 32.60% of eyes with astigmatic error.